ANALISIS HAMBATAN BELAJAR BERDASARKAN KESALAHAN MENYELESAIKAN SOAL MATERI LINGKARAN DI SMPN 13 PONTIANAK - Marlena Marlena; Edy Yusmin; Bistari Bistari (Universitas Tanjungpura, 2021)
AbstractThe purpose of this study was to analyze student learning obstacles from the results oferrors made by students in solving problems on the circle subjeck matter. Thisresearch method is descriptive qualitative. Data collection techniques in this studywere written tests and interviews. The subjects of this study were grade VIII studentsSMPN 13 Pontianak in year 2020/2021. The results showed that the errors thatoccurred were conceptual, procedural and technical errors. And there are sixlearning obstacles found, namely learning obstacle type 1 is learning in sketchingcircles, type 2 learning obstacle is learning obstacles in using rules or formulascorrectly, type 3 learning obstacle is learning obstacle in writing rules or formulaswith appropriate, type 4 learning obstacle is learning obstacle in problem solvingsystematics, type 5 learning obstacle is learning obstacle in understanding questionsand type 6 learning obstacle is learning obstacle in writing degree symbols on thevalue of an angle. And there are three learning obstacles that occur, ontogeny,didactic and epistemological learnng.Keywords: Analysis of learning obstacle, errors, circle probem.